2021
DOI: 10.1016/j.amepre.2020.08.009
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a Community-Level Intervention on Alcohol-Related Motor Vehicle Crashes in California Cities: A Randomized Trial

Abstract: Introduction: This trial assesses the effects of a community-level alcohol prevention intervention in California on alcohol-related motor vehicle crashes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 29 publications
0
16
0
Order By: Relevance
“…For that reason, longer checkpoints will theoretically have stronger effects than shorter checkpoints, although we did not detect such an association. It is possible that other checkpoint features not assessed here, such as accompanying advertising (e.g., marketing blitzes), are more important contributors to checkpoint effectiveness than the precise size and duration of each site (Saltz et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…For that reason, longer checkpoints will theoretically have stronger effects than shorter checkpoints, although we did not detect such an association. It is possible that other checkpoint features not assessed here, such as accompanying advertising (e.g., marketing blitzes), are more important contributors to checkpoint effectiveness than the precise size and duration of each site (Saltz et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Eleven studies included drink driving enforcement activities only, such as RBTs, sobriety checkpoints, saturation patrols, drink driving arrests or a combination of these [19,21,22,26,27,[29][30][31][32][33]36]. An additional seven studies examined the effect of drink driving enforcement coordinated with publicity activities to increase the visibility of the enforcement [17,18,20,24,25,28,34]. One of these was an evaluation of high-visibility drink-driving enforcement demonstration projects in seven US states [25].…”
Section: Types Of Policy Enforcement Activities Studiedmentioning
confidence: 99%
“…Drink driving-related outcomes of interest varied among the studies, with some studies using more than one outcome (n = 5). Studies that focused on alcohol-related traffic crashes (ARTC) as the primary outcome of interest (n = 13) used various measures, including single-vehicle night-time crashes [20,23,24,26,34], number of crashes in which at least one victim was injured and required medical treatment, or in which there was more than $1000 (USD) of property damage [33], crash rate calculated as total driving under the influence (DUI)-related crashes among licensed drivers (multiplied by 1000) [29], alcohol-related fatalities [22,25,36], rate of crashes associated with alcohol-positive driving [21] and crash rates involving at least one driver with a BAC of 0.05 g/ml or greater [19,30].…”
Section: Outcomes Studiedmentioning
confidence: 99%
See 1 more Smart Citation
“…Consistent with general deterrence theory, several systematic reviews of observational studies have found sobriety checkpoints to be associated with decreased incidence of alcohol‐impaired driving and alcohol‐involved crashing [13–16]. Two cluster RCT that test the combined impacts of sobriety checkpoints and other universal prevention strategies provide supporting experimental evidence for their effectiveness [17,18]. Given the consistency and strength of these findings, research on sobriety checkpoints can now move from intervention science (which tests whether an intervention is effective) to implementation science (which tests how an intervention is most effective) [19,20].…”
Section: Introductionmentioning
confidence: 99%